CO2 fixation at atmospheric pressure: porous ZnSnO3 nanocrystals as a highly efficient catalyst for the synthesis of cyclic carbonates. Issue 37 (29th March 2016) - Roy, Susmita; Banerjee, Biplab; Bhaumik, Asim; Islam, Sk. Manirul
Abstract : Self-assembled, ultra small, porous zinc stannate nanocrystals have been synthesized, which catalyzes the formation of cyclic carbonates from various epoxide and CO2 under very mild reaction conditions. Abstract : An efficient methodology for the synthesis of cyclic carbonates from epoxides and CO2 has been developed using self-assembled, ultra small, porous zinc stannate nanocrystals as a catalyst under atmospheric pressure. The catalyst is synthesized by using sodium salicylate as a soft template and the material is thoroughly characterized by powder XRD, HR TEM, N2 -sorption and UV-visible spectroscopic tools. Moreover, the catalyst smoothly catalyzes a wide range of reactants to produce a series of cyclic carbonates in excellent yields, under atmospheric pressure of CO2 and in the presence of PEG-600 as a green solvent. The catalyst can be easily recovered from the reaction medium and be reused without significant loss in its catalytic activity and selectivity, suggesting the future potential of this nanocatalyst in the clean-up of the environment.